Pengaruh Turnover, Etika Islam, dan Kompensasi terhadap Kinerja dengan Moderasi Komitmen pada PT. Primayudha Mandirijaya - Pratama, Brylian; Utomo, Budi (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
In order to improve employee performance, turnover is an important factor that influences employee performance improvement To maximize the quality of employee performance in the company, one of the instruments is Islamic work ethics Improving employee performance is very important for the success of the organization because it has a significant impact on the productivity, efficiency, and competitiveness of the company In this study, the researcher took the object at PT. Primayudha Mandirijaya which is included in a company that has been well organized especially after being held by PT. Sri Rejeki Isman Tbk (Sritex). At PT. Primayudha Mandirijaya experienced various demands, namely, the need for increased employee performance to improve the company's reputation and branding. The purpose of this study is to determine the influence of turnover intention, Islamic work ethics, and compensation on the performance of employees moderated by organizational commitment. This type of research is quantitative research. In this study, the population used was 1,044 employees at PT. Primayudha Mandirijaya. Furthermore, this study used a sample of 100 respondents with several predetermined criteria or purposive sampling techniques. The tests used are data instrument tests, classical assumption tests, and statistical tests. After testing with SPSS version 25, the results were obtained, namely turnover intention has a negative and significant effect on employee performance, Islamic work ethics has a negative and significant effect on employee performance, compensation has a positive and insignificant effect on employee performance, organizational commitment is able to moderate turnover intention on employee performance, organizational commitment is able to moderate Islamic work ethics on employee performance, and the organization's commitment is not able to moderate compensation to employee performance.